Comparison of ExPress Mini-Device Implantation Alone or Combined with Phacoemulsification for the Treatment of Open-Angle Glaucoma - Łukasz Stawowski; Joanna Konopińska; Marta Deniziak; Emil Saeed; Renata Zalewska; Zofia Mariak (Journal of Ophthalmology)
We propose comparative assessment of the effectiveness of two surgical methods for the treatment of open-angle glaucoma: (1) ExPress mini-device implantation combined with phacoemulsification and (2) ExPress mini-device implantation alone. In this prospective study, 81 patients (88 phakic eyes) with uncontrolled open-angle glaucoma enrolled for surgery. They were assigned two groups, those with coexisting cataracts (46 eyes; P-ExPress group) and those with glaucoma alone (42 eyes; ExPress group). The follow-up period was 12.9 ± 0.4 months in P-ExPress and 12.2 ± 0.6 months in ExPress group. In both groups the following parameters were measured: best corrected visual acuity (BCVA), intraocular pressure (IOP), number of complications and necessary postoperative interventions, and number of glaucoma medications. The IOP at the end of follow-up was similar in both groups (18.8 ± 5.9 versus 18.1 ± 4.8 mmHg; P=0.814). There were no statistical differences in the average number of glaucoma medications between ExPress and P-ExPress groups (0.9 ± 1.65 versus 1.3 ± 1.7; P=0.419) as well as in the number of postoperative complications (26 versus 21%; P=0.179 in the P-ExPress and ExPress groups, resp.). Both methods are safe and effective for the surgical treatment of open-angle glaucoma. Coexistence of cataracts does not constitute a compelling contraindication for combined surgery.